A Survey of Securities Laws and Enforcement - Lopez-de-Silanes, Florencio (World Bank, Washington, D.C., 2013)
The author examines the theoretical and empirical literature pertaining to securities laws and their enforcement by regulators and courts to establish what is known and what is yet unclear. Recent empirical research in the field has established that law matters. Mandatory disclosure requirements, insider trading laws, safeguards against self-dealing transactions, adequate regulatory powers, and simple laws that are easily enforced aid in the development of capital markets. The debate is now focused on identifying which components of securities laws matter most and on what the optimal regulatory framework for each country should be. Although public enforcement of securities laws is important, the author finds that the largest impact comes from aspects of the law that facilitate private enforcement. This means that the development of capital markets depends crucially on creating laws that facilitate enforcement and improving court procedures that allow for a more efficient dispute resolution.